Loose women, lecherous men : a feminist philosophy of sex - LeMoncheck, Linda (Oxford University Press, 1997)
The author discusses methods for mediating the tensions among apparently irreconcilable feminist perspectives on women's sexuality and shows how a feminist epistemology and ethic can advance the dialogue in women's sexuality across a broad political spectrum.